Implementation of the Dynamic Learning Model in Strengthening Children's Character Education - Sulaeman Fityan Saputra; Shafwa Marine Pasekoenda; Natalie Beth Evangeline Alficorista; Imam Shofwan (Universitas Negeri Semarang, 2026)
Background - Character development in the learning process is a serious challenge in the world of education, especially in non-formal educational institutions. Purpose - This study aims to describe the learning process through planning, implementation, and evaluation. Method/Approach - This study used a descriptive qualitative method with a phenomenological study design. Findings - The planning process is carried out by setting learning objectives, teaching resources or materials, learning methods, learning media, and designing learning outcome assessments. The learning process begins with a prayer, followed by a reflection on the previous meeting, the delivery of material, and ends with a review of the material covered in the lesson. Summative evaluation is used in the form of crossword puzzles during the learning process. Conclusion - This study shows that Dynamic Learning-based learning can be an effective approach in developing children's character, especially in non-formal educational environments such as in Wonosari Village, Semarang City. Novelty/Originality/Value - Dynamic learning has been proven to change the character of students.